Pengaruh Pajak Hiburan Dan Pajak Reklame Terhadap Pendapatan Asli Daerah - Iis Anisa Yulia (Jurnal Ilmiah Akuntansi Kesatuan, 2020)
This study aims to examine the effect of Entertainment Tax and Advertisement Tax on Regional Original Revenue both partially and simultaneously. The analytical method used is multiple linear regression, with Local Revenue as the dependent variable and Entertainment Tax and Advertisement Tax as the independent variable. By using the data of Entertainment Tax, Advertisement Tax and Regional Original Revenue for five years, namely the period 2014-2018, the results of the study show that partially the Entertainment Tax and Advertising Tax variables have a significant effect on Local Own Revenue, and of the two variables the Entertainment Tax variable has the biggest influence. While simultaneously, the two variables together have a significant effect on the Regional Original Revenue Keywords: Entertainment Tax, Advertisement Tax, Local Revenue